Viaggio e politica - Campos Boralevi, Lea (Firenze University Press, 2010)
After the books on "La politica e gli spazi politici", "Metafore dello spazio", "Gli spazi immaginati", "Spazi e politica nella modernità tecnologica", this notebook continues the series devoted to illustrating the results of an interdisciplinary study group fostered by Lea Campos Boralevi, Vittore Collina and Bruna Consarelli, lecturers in the history of political theory, entitled "Figure dello spazio, politica e società", and aimed at exploring major political and social issues from the aspect of spaces and their production. Devoted to "Viaggio e politica" it seeks to probe the complex manner in which ideas, theories and models have been shaped over the history of political thought in relation to the journey in its spatial and physical, but also symbolic and imaginary, dimension. It is conceived as a moment of encounter and even clash with reality, problems, 'other' mentalities, and with formation, knowledge and transformation. Appendix: Tavole di Zwinger riprodotte nell'intervento di Lucia Felici, "La Methodus Apodemica di Theodor Zwinger: un osservatorio cinquecentesco della città come spazio politico".